2009
DOI: 10.1177/0310057x0903700213
|View full text |Cite
|
Sign up to set email alerts
|

Video and Optic Laryngoscopy Assisted Tracheal Intubation – the New Era

Abstract: With advances in technology, videoscopy and optic intubation have been gaining popularity, particularly in patients with difficult airways or as rescue devices in failed intubation attempts. Their routine use is, however, an uncommon occurrence. This review paper will summarise some of those newly developed devices currently available to assist tracheal intubation, their advantages, disadvantages when compared with the conventional laryngoscope and finally, evidence to support their use in both elective and em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 72 publications
0
29
0
Order By: Relevance
“…These manipulations of the airway have adverse implications from significant hemodynamic disturbance, cervical instability, injury to oral and pharyngeal tissues, and dental damage. [10]…”
Section: Direct Versus Indirect Laryngoscopymentioning
confidence: 99%
See 2 more Smart Citations
“…These manipulations of the airway have adverse implications from significant hemodynamic disturbance, cervical instability, injury to oral and pharyngeal tissues, and dental damage. [10]…”
Section: Direct Versus Indirect Laryngoscopymentioning
confidence: 99%
“…A number of review articles have used different designations for classification of videolaryngoscopes. [1231016] The most commonly used classification is: Macintosh-modification, angulated blade, and tube/guide channel.…”
Section: Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The disadvantage of the AWS ® is that the P blade is 18 mm thick requiring a mouth opening of at least 25 mm[24] and it can only be used for awake intubation through oral route. In our view, the P blade takes up more space in the mouth and, therefore, requires good topical anaesthesia of the oral cavity to make it more tolerable to the awake patient.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have shown that video laryngoscopy is beneficial in that it decreases cervical spine motion during intubation, improves glottic exposure, and increases the chance of first-pass success during difficult intubations compared to direct laryngoscopy (3)(4)(5)(6)(7)(8). Despite this evidentiary support, some believe that video laryngoscopy is not commonly used, and no prior study has evaluated its adoption by emergency departments (EDs) (9).…”
Section: Introductionmentioning
confidence: 99%